Impact evaluation of the use of PBR cowpea in Nigeria: Baseline process evaluation report - Mockshell, Jonathan; Asante-Addo, Collins; Nwagboso, Chibuzo; Ritter, Thea; Amare, Mulubrhan; Andam, Kwaw S. (International Food Policy Research Institute, 2024)
This process evaluation (PE) is part of a five-year (2021–2026) impact evaluation (IE) of the use of a new pod-borer-resistant (PBR) cowpea variety in Nigeria, a project led by the International Food Policy Research Institute (IFPRI) and funded by the United States Agency for International Development (USAID). While the IE draws from a representative sample of 1,399 farmers to determine the causal impacts of the use of PBR cowpea, the PE complements the IE by exploring in detail the potential adoption of the PBR cowpea variety and the reasons for adoption or non adoption, including its potential impacts on actors throughout the value chain. A program impact pathway (PIP) is the basis of this PE. The PIP identifies how impacts emerge from program inputs, processes, outputs, and outcomes to highlight barriers and facilitators of adoption. Given that this PE was conducted before the rollout of PBR cowpea in the IE, the analysis focuses on the potential of this innovative seed to achieve positive outputs and outcomes based on the PIP. Qualitative data were gathered from eight focus group discussions with farmers and 180 semi-structured interviews conducted with farmers, extension agents, seed dealers, and cowpea traders from eight local government areas (LGAs) in the states of Adamawa and Kwara. Given that the data are qualitative, the data are not representative. However, important insights were found that can help guide the IE.